The burden of heart failure in the general population: a clearer and more concerning picture - von Lueder, Thomas G.; Agewall, Stefan (Journal of Thoracic Disease, 2018)
The syndrome of heart failure constitutes a major global health problem. Patients with heart failure exhibit substantial morbidity and poor survival which at best, is similar to cancer (1,2).